The wandering holy man : the life of Barsauma, Christian asceticism, and religious conflict in late antique Palestine - Hahn, Johannes, 1957-; Menze, Volker-Lorenz, 1974- (Transformation of the classical heritage, 2020)
"Barsauma was a fifth-century Syrian ascetic, archimandrite, and leader of monks, notorious for his extreme asceticism and violent anti-Jewish campaigns across the Holy Land. Although Barsauma was a powerful and revered figure in the Eastern church, modern scholarship has widely dismissed him as thug of peripheral interest. Until now, only the most salacious bits of the ancient text the Life of Barsauma-a fascinating collection of miracles that Barsauma undertook in the Holy Land-had been translated. This pioneering study includes the first full translation of the Life and a series of studies by scholars employing a range of methods to illuminate the text from different angles and contexts. This is the authoritative collection on this influential but understudied figure in the history of the church and his life, travels, and relations with other religious groups"--